Cyberbullying phenomenon on instagram social media: phenomenological analysis of indonesian students - Larasati, Sectio Putri (JPGI (Jurnal Penelitian Guru Indonesia), 2024)
With the rapid increase in the use of internet technology among the community, teenagers and children are increasingly unable to control themselves in using the internet, especially on social media which increases the impact of the phenomenon of cybercrime (cyberbullying), especially on Instagram social media. Cyberbullying is a form of play and aggressive behavior against someone that is carried out continuously in cyberspace through an internet connection, cyberbullying has a negative impact so that it cannot be directed to the location, cyberbullying can be ridicule, threats, fraud, insults, defamation, stalking or hacking. Thus, it is necessary to study further to analyze the terms of early prevention efforts. This paper has a purpose, namely to see and trigger that cyberbullying behavior on social media, especially among Indonesian students, is increasingly widespread. Although cyberbullying is still ignored in Indonesia, it will have fatal consequences for teenagers in the future.